Isolation and Identification of Four Strains of Bacteria with Potential to Biodegrade Polyethylene and Polypropylene from Mangrove - Xilin Fang; Zeming Cai; Xiaocui Wang; Ziyu Liu; Yongkang Lin; Minqian Li; Han Gong; Muting Yan (Microorganisms, 2024)
With the rapid growth of global plastic production, the degradation of microplastics (MPs) has received widespread attention, and the search for efficient biodegradation pathways has become a hot topic. The aim of this study was to screen mangrove sediment and surface water for bacteria capable of degrading polyethylene (PE) and polypropylene (PP) MPs. In this study, two strains of PE-degrading bacteria and two strains of PP-degrading candidate bacteria were obtained from mangrove, named Pseudomonas sp. strain GIA7, Bacillus cereus strain GIA17, Acinetobacter sp. strain GIB8, and Bacillus cereus strain GIB10. The results showed that the degradation rate of the bacteria increased gradually with the increase in degradation time for 60 days. Most of the MP-degrading bacteria had higher degradation rates in the presence of weak acid. The appropriate addition of Mg2+ and K+ was favorable to improve the degradation rate of MPs. Interestingly, high salt concentration inhibited the biodegradation of MPs. Results of scanning electron microscopy (SEM), atomic force microscopy (AFM), and Fourier-transform infrared spectroscopy (FTIR) indicated the degradation and surface changes of PP and PE MPs caused by candidate bacteria, which may depend on the biodegradation-related enzymes laccase and lipase. Our results indicated that these four bacterial strains may contribute to the biodegradation of MPs in the mangrove environment.